Decoding Leptin: Unraveling the Role of Leptin Signaling in the BattleagainstObesity - Singha, Soumyadip; Nayak, Soumyadip; Bishayee, Rahul; Sarkar, Pritam; Ghosh, Priyanka; Dutta, Udita; Mishra, Poulomi (Indian Journal of Pharmacy & Drug Studies, 2024)
Obesity represents a major global health crisis, linked to a spectrum of metabolic disorders, including diabetes, cardiovascular diseases, and hypertension. Leptin, a hormone predominantly produced by adipose tissue, plays a critical role in regulating energy balance, appetite, and metabolism. Historically, leptin was believed to be a cornerstone in the management of obesity due to its ability to suppress appetite. However, the effectiveness of leptin therapy has been limited by the phenomenon of leptin resistance in obese individuals. This review, titled "Decoding Leptin: Unraveling the Role of Leptin Signaling in the Battle Against Obesity," aims to delve into the molecular intricacies of leptin signaling pathways and their implications in obesity management. We explore the mechanisms underlying leptin resistance, the impact of leptin on neuroendocrine pathways, and the potential for resetting leptin sensitivity as a therapeutic strategy. Additionally, we discuss recent advances in therapeutic approaches aiming to enhance leptin sensitivity or mimic its effects, including novel pharmacological agents and lifestyle modifications that influence leptin signaling. By providing a comprehensive overview of current research and emerging therapies, this review seeks to illuminate the path forward in leveraging leptin signaling for more effective obesity interventions.